A new delivery system based on apple pomace–pectin gels to encourage the viability of antimicrobial strains. (April 2020) - Juodeikiene, Grazina; Zadeike, Daiva; Bartkiene, Elena; Lėlė, Vita; Bernatoniene, Jurga; Jakštas, Valdas
This work was aimed to investigate the concept of the valorization of apple processing by-products to produce a new preservation system based on apple pomace gels to encourage the viability of antimicrobial Lactobacillus strains. A high frequency (850 kHz) low power (1.3 W/cm 2 ) ultrasound-stimulated cavitation was used for the structure modulating of gels under low-temperature (50 ℃) conditions. Medium esterified apple pectin was added to apple pomace to improve its texture properties and stability. The monitoring of the process of gelation was performed by using acoustic technique and method, based on the measurement of the distance (parameter h, mm) traveled by a free-falling module. The obtained data were then compared to gel texture measurements. The results suggest that low power ultrasound leads to a reduced jelly mass stickiness and increased gel hardness, compared to the thermally treated sample. The immobilization of probiotic cells in low pectin apple pomace gels did not sufficiently protect the microorganisms. The higher viability of immobilized Lactobacillus paracasei (54–77%) compared to L. plantarum (43–59%) was recorded after incubation at acidic conditions (pH 2.0). The most suitable system for preserving bacterial cells during storage can be the apple pomace–pectin gel containing up to 53% pectin as a stabilizer retaining 84% of viable cells after one-month storage at 4 ℃. The apple pomace–pectin hydrogels with gelation rate ( dh / dt ) of 0.03–0.05 mm/s can be used for the preservation of bacterial cells as a suitable functional ingredient for food.